Exploring the cancer risk perception and interest in genetic services among Indigenous people in Queensland, Australia - Christina M. Bernardes; Patricia C. Valery; Gail Garvey (Australian and New Zealand Journal of Public Health, 2014)
Abstract Objective: The purpose of this study is to explore the levels of interest among Indigenous people with cancer in identifying cancer risk in their family and seeking genetic counselling/testing. Design and setting: A cross‐sectional survey of Indigenous cancer patients recruited from four major treating hospitals in Queensland. Participants’ family history of cancer and interest in genetic counselling/testing was sought using a structured questionnaire. Results: Overall, 73.0% of 252 participants reported having a family history of cancer; of those, 52.8% had at least one first‐degree relative with cancer. A total of 68.3% of participants indicated concern about relatives being affected by cancer and 54.4% of participants indicated they would like to assess the cancer risk in their family with a specialist. Concern was associated with willingness to discuss the risk of cancer with a specialist (p<0.001). Conclusions: Indigenous cancer patients do have a family history of cancer and appear willing to undergo genetic counselling/investigation. It is of great concern that this population could miss the benefits of the technological advances in health care, creating a much larger disparity in health outcomes. Implications: Health service providers should not assume that Indigenous cancer patients will not follow their recommendations when referred to genetic counselling/investigation services.